Altered white matter diffusivity and subtle motor function in a pilot cohort of adolescents with sports-related concussion. (23rd February 2022) - Crasta, Jewel E.; Tucker, Robert N.; Robinson, Joshua; Chen, Hsuan Wei; Crocetti, Deana; Suskauer, Stacy J.
ABSTRACT: Background and objective: Adolescents with sports-related concussion (SRC) demonstrate acute and persistent deficits in subtle motor function. However, there is limited research examining related neurological underpinnings. This pilot study examined changes in motor-associated white matter pathways using diffusion tensor imaging (DTI) and their relationship with subtle motor function. Methods: Twelve adolescents with SRC (12–17 years) within two-weeks post-injury and 13 never-injured neurotypical peers completed DTI scanning. A subset of 6 adolescents with SRC returned for a follow-up visit post-medical clearance from concussion. Subtle motor function was evaluated using the Physical and Neurological Examination of Subtle Signs (PANESS). Results: Adolescents with SRC showed higher mean diffusivity (MD) of the superior corona radiata and greater subtle motor deficits compared to controls. Across all participants, greater subtle motor deficits were associated with higher (more atypical) MD of the superior corona radiata. Preliminary longitudinal analysis indicated reduction in fractional anisotropy of the corpus callosum but no change in the MD of the superior corona radiata from the initial visit to the follow-up visit post-medical clearance. Conclusions: These findings support preliminary evidence for a brain–behavior relationship between superior corona radiata microstructure and subtle motor deficits in adolescents with SRC that merits further investigation.